Attack angle, resultant speed and acceleration of the hand and vertical acceleration of the greater trochanter during sculling motion: a case study - Gomes, L. E.; Loss, J. F. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Synchronised swimmers need to be able to maintain a steady height in the water by performing controlled sculling motion, in which constant vertical resultant force (VRF) is applied. This study aimed to analyse the attack angle, the resultant speed and acceleration of the hand during sculling motion in order to relate these variables with the vertical acceleration of the greater trochanter (VAGT), which is proportional to the VRF. METHODS: One synchronised swimmer was asked to perform sculling motion in a stationary, vertical position (head above the water surface and with the water at chin level). Three-dimensional kinematic data from underwater video analysis was used to calculate the VAGT, the average attack angle and the hand`s average resultant speed and acceleration during 11 consecutive cycles of sculling motion. Each cycle was divided into four phases: in-sweep, transition phase from in-sweep to out-sweep, out-sweep and transition phase from out-sweep to in-sweep (Arellano et al., 2006). Each variable was compared between the phases through a series of paired t-tests ( =0.05). RESULTS: Greater attack angles were found during the transition phase from out-sweep to in-sweep (51.8±6.8°). This phase also presented higher average resultant acceleration of the hand (27.4±4.8 m/s2). Higher average resultant speeds of the hand were found during the in-sweep and out-sweep (1.8±0.2 m/s). The lowest average attack angle (1.2±9°) and resultant speed of the hand (1.4±0.1 m/s) occurred during the out-sweep and transition phase from in-sweep to out-sweep respectively. The highest positive values of the VAGT occurred during the transition phase from out-sweep to in-sweep (0.8±0.2 m/s2), while the highest absolute negative values occurred during the other transition phase (-0.7±0.2 m/s2) and the lowest absolute average occurred during the in-sweep (-0.1±0.2 m/s2). DISCUSSION: Comparing insweep and out-sweep, greater VRF was applied during the out-sweep, which also showed the lower attack angle. Greater negative VRF was found during the transition phase from in-sweep to out-sweep, which may be explained by the lower average attack angle, while greater positive VRF was found during the other transition phase in which average attack angle was higher.